Assessment of Knowledge Perception and Attitudes on Medications in General Population - K, Aishwaryalakshmi; B, Sasikala; N, Sreelalitha; E, Vigneshwaran; YR, Padmanabha (Indian Journal of Pharmacy Practice)
Modern medicines have changed the way in which diseases are managed and controlled. Despite all their benefits, evidence continues to mount that adverse reactions to medicines are common, yet often preventable, cause of illness, disability and even death. The objective of the present study was to explore the perceptions and knowledge regarding ideas about the medication and as well as adherence in general population. A questionnaire was developed to assess both attitudes towards medications as well as self-medication. Our study found that the patients who received family assistance in managing their medications often lacked an understanding of some of their own treatments. Most of the respondents have taken medications from the pharmacists only, which shows there is greater chance and opportunity for the pharmacists in guiding and providing proper education to the patients.